Pendekatan Highest and Best Use dalam Pelestarian Bangunan Bersejarah - Danastri Yuwono, Aisyah Pratita; Khairunnisa, Amanda Aufa; Ikasanti, Mesa Noor; Adilah, Nada Haifa; Widiyani, Widiyani (Universitas Sebelas Maret Surakarta, 2023)
The concept of